Aplikasi Penentuan Program Studi Calon Mahasiswa Menggunakan Simple Additive Weighting - Siti Ratna Sari; Nahdi Saubari; Muhammad Syahid Pebriadi (Journal of Applied Computer Science and Technology, 2020)
Decision support systems are part of computer-based information systems that are commonly used to support decision making in an organization or company. The decision support system is used as an alternative system that helps in making decisions to recommend the selection of study programs to prospective engineering faculty students. This decision support system uses the Simple Additive Weighting (SAW) method. The SAW method in this study uses five criteria, namely the value of mathematics, the value of English, the value of technology education, the value of cultural arts, and the income of parents. There are four alternatives used, namely Informatics, Civil Engineering, Architecture, and Urban and Regional Planning (PWK).